A secure and easy-to-implement web-based communication framework for caregiving robot teams - Tuna, G.; Das, R.; Tuna, A.; Orenbas, H.; Baykara, M.; Gulez, K. (Iop Publishing Ltd, 2016)
In recent years, robots have started to become more commonplace in our lives, from factory floors to museums, festivals and shows. They have started to change how we work and play. With an increase in the population of the elderly, they have also been started to be used for caregiving services, and hence many countries have been investing in the robot development. The advancements in robotics and wireless communications has led to the emergence of autonomous caregiving robot teams which cooperate to accomplish a set of tasks assigned by human operators. Although wireless communications and devices are flexible and convenient, they are vulnerable to many risks compared to traditional wired networks. Since robots with wireless communication capability transmit all data types, including sensory, coordination, and control, through radio frequencies, they are open to intruders and attackers unless protected and their openness may lead to many security issues such as data theft, passive listening, and service interruption. In this paper, a secure web-based communication framework is proposed to address potential security threats due to wireless communication in robot-robot and human-robot interaction. The proposed framework is simple and practical, and can be used by caregiving robot teams in the exchange of sensory data as well as coordination and control data.
5th International Conference on Materials and Applications for Sensors and Transducers (IC-MAST) -- SEP 27-30, 2015 -- Mykonos, GREECE